Comparison of the Implementation of SAK EMKM and SAK ETAP in MSME RM. Nusantara Grilled Fish Cikarang - Bekasi - Dewi, Mutiah Puspa; Yulia, Iis Anisa; Marnilin, Feni (Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to determine the comparison between the financial reports of SAK EMKM and SAK ETAP for MSMEs. This research is a type of quantitative research using a descriptive approach in data collection. The data processed is the financial report of RM Ikan Bakar Nusantara UMKM. The data collection and processing techniques use observation and documentation methods. Meanwhile, the data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The research results show that the UMKM RM Ikan Bakar Nusantara prepares its financial reports using SAK EMKM which is easier to understand compared to SAK ETAP and the financial reports presented are profit and loss reports, reports of changes in equity, and financial reports. The conformity of SAK EMKM to the financial statements of RM Ikan Bakar Nusantara UMKM is fully compliant. . Keywords: MSME, Financial Reports, SAK EMKM, SAK ETAP